Synchronizing with the rhythm: Infant neural entrainment to complex musical and speech stimuli - Cantiani, Chiara; Dondena, Chiara; Molteni, Massimo; Riva, Valentina; Piazza, Caterina (Frontiers in Psychology, 2022)
Neural entrainment is defined as the process whereby brain activity, and more specifically neuronal oscillations measured by EEG, synchronize with exogenous stimulus rhythms. Despite the importance that neural oscillations have assumed in the last years in the field of auditory neuroscience and speech perception, in human infants the oscillatory brain rhythms and their synchronization with complex auditory exogenous rhythms is still relatively unexplored. In the present study, we investigate infant neural entrainment to complex non-speech (musical) and speech rhythmic stimuli; we provide a developmental analysis to explore potential similarities and differences between infants’ and adults’ ability to entrain to the stimuli; and we analyze the associations between infants’ neural entrainment measures and the concurrent level of development. 25 8-month-old infants were included in the study. Their EEG signals were recorded while they passively listened to non-speech and speech rhythmic stimuli modulated at different rates. In addition, Bayley Scales were administered to all infants to assess their cognitive, language, and social-emotional development. Neural entrainment to the incoming rhythms was measured in the form of peaks emerging from the EEG spectrum at frequencies corresponding to the rhythm envelope. Analyses of the EEG spectrum revealed clear responses above the noise floor at frequencies corresponding to the rhythm envelope, suggesting that – similarly to adults – infants at 8 months of age were capable to entrain to the incoming complex auditory rhythms. Infants’ measures of neural entrainment were associated to concurrent measures of cognitive and social-emotional development.